Value Children Dalam Budaya Adat: Eksistensi Anak Laki-laki Pada Keluarga Suku Komering - Chici Rima Putri Pratama (An Nisa'a, 2017)
Value of children the child value is associated with the culture within a single family. The study in this paper on the existence of the boys in her contribution to the family in the culture of South Sumatra with a focus of indigenous Histories. The assumption that appears in the custom that the Histories that more boys believed to have eternal soul more to appease his parents in the world and in the hereafter. So it is very important the value of older men in the life of a family in the tribe of the indigenous Histories so that married couples are generally more expecting the birth of boys than girls.